The characterisation of aerosol particle contamination as the result of carry-over and cross-over in enthalpy wheels. (29th November 2010) - Handy, Rodney G.; Rodgers, Kevin; Wang, Jon; Tumey, Matt; Rodriguez, Danny; Hutzel, William
This paper provides results from a study that characterised the particle distributions found from variable contaminated airstreams in energy recovery ventilators (ERV) during two different test scenarios. The first scenario involved the measurement of the particulate concentrations during an operational situation when the pressure differential forces cross-flow leakage between the exhaust and intake streams. The second scenario involved the characterisation of aerosol particulate concentrations from the carry-over contamination when the wheel was not in operation. The findings from the study concluded that if a source of aerosol particulate matter is present in an environment utilising an ERV system, then cross-over and carry-over contamination will occur proportionally to the amount of aerosol particulate matter released into the system.